The Effects of Methylphenidate on Resting-State Functional Connectivity of the Basal Nucleus of Meynert, Locus Coeruleus, and Ventral Tegmental Area in Healthy Adults - Kline, Ryan L.; Zhang, Sheng; Farr, Olivia M.; Hu, Sien; Zaborszky, Laszlo; Samanez-Larkin, Gregory R.; Li, Chiang-Shan R. (Frontiers in Human Neuroscience, 2016)
Background: Methylphenidate (MPH) influences catecholaminergic signaling. Extant work examined the effects of MPH on the neural circuits of attention and cognitive control, but few studies have investigated the effect of MPH on the brain’s resting-state functional connectivity (rsFC). Methods: In this observational study, we compared rsFC of a group of 24 healthy adults who were administered an oral 45 mg dose of MPH with a group of 24 age and gender matched controls who did not receive MPH. We focused on three seed regions: basal nucleus of Meynert (BNM), locus coeruleus (LC), and ventral tegmental area/substantia nigra, pars compacta (VTA/SNc), each providing cholinergic, noradrenergic and dopaminergic inputs to the cerebral cortex. Images were pre-processed and analyzed as in our recent work [1-2]. We used one-sample t test to characterize group-specific rsFC of each seed region and two-sample t test to compare rsFC between groups. Results: MPH reversed negative connectivity between BNM and precentral gyri. MPH reduced positive connectivity between LC and cerebellum, and induced positive connectivity between LC and right hippocampus. MPH decreased positive VTA/SNc connectivity to the cerebellum, and reduced negative connectivity to left middle occipital gyrus. Conclusion: MPH had distinct effects on the rsFC of BNM, LC, and VTA/SNc in healthy adults. These new findings may further our understanding of the role of catecholaminergic signaling in Attention Deficit Hyperactivity Disorder (ADHD) and Parkinson’s disease and provide insights into the therapeutic mechanisms of MPH in the treatment of clinical conditions that implicate catecholaminergic dysfunction.